Design for lateral stability of slender timber beams considering slip in the lateral bracing system. (November 2018) - Klasson, Anders; Crocetti, Roberto; Björnsson, Ivar; Frühwald Hansson, Eva
Abstract: The present study investigates the significance of potential slip in the bracings of simply supported slender timber members. Three bracing configurations are considered. The first case is that of a timber beam braced at one point at mid-span, the second one braced at two points and the third one braced at three points. Possible slip in the bracing members can for example be due to joint deformation, initial crookedness of purlins and slack (or relaxation) of cables in the stabilizing bay (catenary action). In this study, it is shown that slip in the bracing system can result in a reduced load-bearing capacity (due to larger beam stresses) of the beams. Also, the greater the slip, the greater lateral deflections and consequent bracing forces of the braced member. A simplified approach, using a larger initial geometrical imperfection, to account for potential slip in bracings is also evaluated. This approach is found to work reasonably well in terms of stresses and bracing forces, but underestimates the lateral displacements.